Methods of measuring operational risk and their influence on the level of bank’s capital adequacy - Dziwok, Ewa (Metody pomiaru ryzyka operacyjnego i ich wpływ na poziom adekwatności kapitałowej banku, 2018)
An increasing complication of the financial system with new products, international connections between institutions, the large scale of mergers and acquisitions and the process of globalization have a huge influence on the process of risk measurement and management in banks. Operational risk, which is one of the main financial risks in the bank (together with credit and market risk) differs from the others. Widely understood as the risk associated with a daily activity of the bank, it is defined as the risk of loss resulting from inadequate or failed internal processes, people and systems, or from external events. The purpose of this article is to compare the methods of measuring operational risk in relation to the amount of capital necessary to cover it
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics, 2018, Nr 519, s. 53-62
Keywords: operational risk; capital adequacy; risk measurement; pomiar ryzyka; ryzyko operacyjne; adekwatność kapitałowa